Measuring beliefs about taking hypoglycaemic medication among people with Type 2 diabetes. - Farmer, A; Kinmonth, A; Sutton, S (2006)
AIMS: Identifying patients' beliefs about taking medication can inform interventions to support medication taking, and their evaluation. We set out to establish the range of these beliefs, and measure the frequency of commonly held beliefs and their correlation with intention to take medication and self-reported medication adherence. METHODS: An exploratory survey among Type 2 diabetic patients aged 40 years or older, registered in general practice, used a questionnaire measuring a range of plausible beliefs about taking and intention to take medication developed from interviews where belief elicitation was guided by the Theory of Planned Behaviour. The Medication Adherence Report Schedule was used as a self-report adherence measure. RESULTS: Questionnaires were returned by 121 (61.7%) people. The majority strongly agreed with statements about the benefits of taking medication. Negative beliefs that taking medication would 'cause unpleasant side effects' and 'lead to weight gain' were held by 32.8 [corrected] and 13.9% of people, respectively. Beliefs about benefit were strongly associated with intention to take medication regularly. Two beliefs were associated with reduced medication adherence: 'changes to my daily routine would make it more difficult to take my diabetes medicines regularly' (P < 0.001), and 'if I were to take my diabetes medicines regularly this would lead to my gaining weight' (P < 0.01) [corrected] CONCLUSIONS: Use of a theoretical model to elicit and identify common beliefs about taking medication regularly underscores the importance of exploring weight-gain concerns and how to keep taking tablets when routines change. Beliefs associated with intention and taking medication will inform intervention development, implementation and evaluation in randomized controlled studies.